Analisis Faktor Internal Dan Eksternal Yang Mempengaruhi Kinerja Bank Umum Di Indonesia Periode 2008-2011 - Octaviyanty, Kamalia (Program Doktor Ilmu Ekonomi, 2013)
Banks are the most important financial institutions affect the economy both micro and macro. To assess the growth of the banking industry is not only seen from the banking internal factors but its need to consider to the sensitivity of the banking sector to external factors such as macroeconomic conditions. This study aimed to analyze the influence of external and internal factors to the bank’s performance in IndonesiaFinancial data derived from the financial statements publications issued by Bank Indonesia and the Central Bureau of Statistics for the period 2008-2011. Total population in this study were 111 banks and samples used were 28 banks selected by using purposive random sampling. The data analysis used is the analysis of Structural Equation Modelling (SEM).The results showed that (1) external factors have significant influence to the operatio-nal policies and the bank’s performance, (2) internal factors have significant influence to the operational policies and the bank’s performance, and (3) operational policies have a significant influence to the bank’s performance. The results of this research can be used to guide, either by bank management in managing the company to improve their perfor-mance or investors in investing.Keywords: Internal Factors, External Factors, Operational Policies, Bank’s Performance